Academic motivation and affective engagement toward science and math: the mediating role of self-efficacy - Valenzuela-Peñuñuri, Rosalba; Tapia-Fonllem, César O.; Fraijo-Sing, Blanca S.; Manríquez-Betanzos, Juan Carlos (Frontiers in Education, 2024)
The relationship between career choice and academic achievement associated with science, technology, engineering, and mathematics (STEM) fields has been extensively studied from the Educational Psychology Approach. The present study examined the impact of academic motivation on affective engagement, focusing on the mediating role of self-efficacy in pre-college students. A sample of 324 students between 17 and 19 years (M= 17.41; SD= .506; 51% females, 49% males) from different schools located in northwestern Mexico participated in completing a self-report questionnaire about math and science engagement, self-efficacy to science and math, and academic motivation. Statistical analyses were carried out to determine the reliability and validity of the measurement scale; posteriorly, a mediation analysis was used to determinate the direct and indirect effects of the structural model. The results revealed high correlations between the three study variables. Both mediation analysis and structural equation modeling indicated that academic motivation influences affective engagement through its relationship with self-efficacy. Although self-efficacy has a direct effect on affective engagement, it is also affected by academic motivation, so the interaction between these two generates an influence on affective engagement. In this research, a strong relationship was observed between academic motivation and self-efficacy, indicating that students who are motivated and enjoy performing activities related to their science and math classes have previous experiences of success in these tasks. These results provide new insights for the improvement of strategies regarding the training and performance of pre-university students in the areas of science and mathematics by considering their affective states.